Fog hanging in over the Wester Cove - Branch Cultural Historical Association (2010)
Starting at the Hayjers Rock, the Wester Cove bends in toward the Place on the west side of the River. Cliffs divide the Wester Cove into two parts: tree-covered hills that range toward the Place, and a narrow, rugged shoreline at the base of the cliffs. Over the years, the hills closest to the Place have been cleared for farming while those further out still have their trees and are traversed by footpaths, sheep paths, slide paths, rabbit paths, fox paths and ATV trails.